Bending behavior of hybrid sandwich composite structures containing 3D printed PLA lattice cores and magnesium alloy face sheets. Issue 11 (18th August 2022) - Zhou, Xia; Li, Junlei; Qu, Chi; Bu, Wenming; Liu, Zifan; Fan, Yafu; Bao, George
ABSTRACT: In this study, the bending behavior of novel magnesium alloy facesheet and 3D-printed polylactic acid (PLA) lattice core sandwich panels with enhanced interface adhesion has been investigated by joint experiment and simulation method. A reliable numerical model for predicting three-point bending behavior of hybrid sandwich panels was developed and an explicit finite element analysis using ABAQUS/Explicit with a self-written VUMAT user subroutine was conducted. Meanwhile, hybrid sandwich panels were evaluated experimentally by three-point bending tests in order to validate the results obtained in the FEA. The comparison results have shown that the FEA predictions are consistent with the experimental tests. The bending resistance of the hybrid PLA core/Mg alloy composite sandwich panel is better than that of the integrated PLA sandwich panel. Among the four lattice geometries studied, namely body-centered cubic (BCC), BCC with gradient distribution of struts (BCCG), BCC with vertical struts connecting all nodes (BCCV), and face and body centered cubic unit cell with vertical struts (F2 BCCZ), the sandwich structure with BCCV lattice cores has the better bending bearing capacity. The core configuration and core density have a coupling effect on the bending properties and failure modes of the hybrid sandwich panels.